Babylonian Historical-Literary Texts - Grayson, A. K. (1975)
Akkadian Prophecies, copy BM 52028 = 82-3-23,3062; The Dynastic Prophecy, BM 40623 = 81-4-28,168; Babylonian Historical Epics; Epic Fragment about the Kassite Period, BM 35322 = Sp. II,893; Adad-shuma-usur Epic, BM 34104 + = Sp. 204+; Nabopolassar Epic, BM 34793 = Sp. II, 286 + 525; Evil-Merodach Epic, BM 34113 = Sp. 213; Epic Fragment, BM 45684= 81-7-6,84; Fragments, BM 34716 = Sp. II, 205, Rm. 742, BM 36692 = 80-6-17,424, BM 35792 = Sp. III, 319, BM 50857 = 82-3-23, 1851.